Enhancing heritage and additional language learning in the preschool years: longitudinal implementation of the Little Multilingual Minds program - Escudero, Paola; Pino Escobar, Gloria; Diskin-Holdaway, Chloé; Hajek, John (Frontiers in Language Sciences, 2025)
Little Multilingual Minds (LMM) partners with universities, communities, and early childhood centers to offer a language exposure program for heritage language (HL) and additional language (AL) speakers in a naturalistic, play-based environment. This paper reports on two program implementations conducted in a Spanish-English bilingual preschool in Sydney, Australia. Implementation 1 focused on HL Spanish children (n = 11; Mage = 4.24) for HL maintenance over 8 months, while Implementation 2 included both HL and AL children (n = 27; Mage = 2.93) with a new cohort over 1 year. Both implementations were quantitatively evaluated in three key areas: HL Spanish linguistic proficiency (vocabulary, listening, speaking, literacy/numeracy), alignment with educational principles (disposition, interaction, interest), and task-related precursors of school readiness (attention, cooperation, engagement), using Bayesian modeling for reliable statistical testing. Results from Implementation 1 showed significant improvements in HL children's linguistic skills from the first to the last assessment, effectively strengthening HL Spanish proficiency while preventing a shift toward English. In Implementation 2, despite challenges, the program was successfully adapted to accommodate both HL and AL children in the same session, yielding encouraging outcomes for both groups. We discuss these findings in terms of their implications for successful HL maintenance and AL learning within preschool classes with mixed language backgrounds.